AUDIT ENERGI DAN MONITORING BERBASIS IOT UNTUK PENINGKATAN EFISIENSI PENGGUNAAN LISTRIK DI ART CENTER DENPASAR - Putranto, Novian Bayu; Dharma, Agus; Rhamani Suryadhi, Putu Ayu (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUM, 2022)
An energy audit is needed to find out energy saving opportunities (PHE) so that it will reduce the amount of electricity bills at the Denpasar Art Center which is used as a cultural performance center in Bali. A more specific location in this research is the Ksirarnawa Art Center Denpasar Building in the lighting section. The energy audit in this study is combined with an IoT-based electrical energy monitoring tool so that electricity usage can be monitored in real time. This IoT-based electrical energy monitoring uses Arduino Nano as a data processor as well as sending data to a site service called Thingspeak to record and display data from sensors. The sensors used are the ZMPT101B voltage sensor and the YHDC SCT 013-000 current sensor which are integrated with the NodeMCU as a module to connect to a wireless network. The results of the energy audit at the Denpasar Art Center got a potential Energy Saving Opportunity (PHE) of 33.6% with suggestions to related parties being to replace lamps using LEDs and to regularly set on/off times.